2007
DOI: 10.2196/jmir.9.3.e23
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perspectives on the Development of a Virtual Clinic for Diabetes Care: Qualitative Study

Abstract: Background The development of the Internet has created new opportunities for health care provision, including its use as a tool to aid the self-management of chronic conditions. We studied stakeholder reactions to an Internet-based “virtual clinic,” which would allow people with diabetes to communicate with their health care providers, find information about their condition, and share information and support with other users.Objective The aim of the study was to present the results of a detailed consultation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…106 Stakeholders believed that younger diabetic patients or those comfortable with technology would more likely benefit from virtual clinics. 107 It was suggested that adults with low literacy levels could benefit from e-health interventions, although concerns were also expressed around oversimplified interventions being perceived as too basic 108 or that patients might be misunderstood and unable to express themselves adequately in relation to computerised CBT. 98 Online CBT was perceived as particularly beneficial for patients familiar with computers.…”
Section: An Evidence Synthesis Of Telehealth Interventions For Long-tmentioning
confidence: 99%
See 1 more Smart Citation
“…106 Stakeholders believed that younger diabetic patients or those comfortable with technology would more likely benefit from virtual clinics. 107 It was suggested that adults with low literacy levels could benefit from e-health interventions, although concerns were also expressed around oversimplified interventions being perceived as too basic 108 or that patients might be misunderstood and unable to express themselves adequately in relation to computerised CBT. 98 Online CBT was perceived as particularly beneficial for patients familiar with computers.…”
Section: An Evidence Synthesis Of Telehealth Interventions For Long-tmentioning
confidence: 99%
“…Internet programmes may require some level of basic training and web-based interventions were more accessible to patients who were familiar or comfortable with using the internet. 98,107 Less computer-literate users expressed concerns over being misunderstood 105 and older people reported fear. 105 Evidence of fit with daily life…”
Section: Evidence Of Fit With Patient Needsmentioning
confidence: 99%
“…With improved availability of internet technologies virtual clinics may offer a technology-supported alternative to members of a group being present in person. 139 In addition, the relatively good performance of automated telephone disease management systems as a comparator for group clinics suggests that, for some patients at least, support might be offered via such technologies. 77,78 These weekly, rotating automated (prerecorded) telephone calls take between 6 and 12 minutes to complete with any 'out of range' responses triggering a personal call back by a nurse manager.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Moreover, Vankatesh's Unified Theory of Acceptance and Use of Technology (UTAUT) explains current performance and use behaviour explain a large proportion of the variance in the intention to use a new technology [22,23]. In addition, a few studies identified patients' preferences for e-health in rehabilitation by using a qualitative research design [7,24,25]. These studies found that patients with cancer and diabetes were willing to use ICT in (rehabilitation) care for self-monitoring of symptoms, web-based physical exercise programs [7], communication with peers [24,25] and access to their health record [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few studies identified patients' preferences for e-health in rehabilitation by using a qualitative research design [7,24,25]. These studies found that patients with cancer and diabetes were willing to use ICT in (rehabilitation) care for self-monitoring of symptoms, web-based physical exercise programs [7], communication with peers [24,25] and access to their health record [7]. However, a lack of studies with a quantitative design impaired generalization of results and so far it is unclear what usage preferences are for other patient groups in rehabilitation care.…”
Section: Introductionmentioning
confidence: 99%